2013
DOI: 10.1002/syn.21716
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic remodeling in the adolescent medial prefrontal cortex and the basolateral amygdala of male and female rats

Abstract: There is recent evidence of continuing development throughout adolescence in two neural areas involved in emotion and cognition, the basolateral amygdala (BLN) and the medial prefrontal cortex (mPFC). Previous research from our laboratory has demonstrated a cellular loss in both of these brain regions in rats between postnatal day (P) 35 and 90. This study investigates dendritic changes in pyramidal neurons of the BLN and Layer 5 of the mPFC at P20 (juvenile), 35 (puberty), and 90 (adulthood) in hooded rats of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(167 citation statements)
references
References 71 publications
7
144
2
2
Order By: Relevance
“…Studies examining plasma and brain levels of stimulants have found that adolescents have lower (Spear and Brake 1983;Kokoshka et al 2000;McCarthy et al 2004;Craig et al 2014), higher (Caster et al, 2005), or similar levels (McCarthy et al, 2004;Caster et al, 2005) compared to adults. Based on the extensive changes occurring in the brain during adolescence (Andersen et al 1997(Andersen et al , 2000Dagher et al 2001;Koss et al 2014;Juraska and Willing 2017), another possibility is that differences in pharmacodynamics (e.g. dopamine transporter function; Volz et al, 2009) contribute to our findings.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies examining plasma and brain levels of stimulants have found that adolescents have lower (Spear and Brake 1983;Kokoshka et al 2000;McCarthy et al 2004;Craig et al 2014), higher (Caster et al, 2005), or similar levels (McCarthy et al, 2004;Caster et al, 2005) compared to adults. Based on the extensive changes occurring in the brain during adolescence (Andersen et al 1997(Andersen et al , 2000Dagher et al 2001;Koss et al 2014;Juraska and Willing 2017), another possibility is that differences in pharmacodynamics (e.g. dopamine transporter function; Volz et al, 2009) contribute to our findings.…”
Section: Discussionmentioning
confidence: 93%
“…Similar developmentally regulated changes have been observed in rodents during their adolescent period, which has been argued to range from as early as postnatal day (P) 28 to at least P60 based on social, cognitive, hormonal, and neurophysiological changes that parallel markers of human adolescence (Tirelli et al 2003;Spear 2011). For example, during rodent adolescence there are significant increases in connectivity between the basolateral amygdala and medial prefrontal cortex (Cunningham et al 2002(Cunningham et al , 2008, changes in the density of monoamine transporters (Moll et al 2000;Bradshaw et al 2016), increases in prefrontal cortex dopamine innervation (Kalsbeek et al 1988), decreases in medial prefrontal cortex neuron number (Markham et al 2007;Willing and Juraska 2015), and reorganization of the amygdala (Rubinow and Juraska 2009;Koss et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…This may reflect differences in the developmental maturation of the MPFC in males compared to females as sex differences A c c e p t e d M a n u s c r i p t 11 are apparent in the adolescent-young adult developmental trajectory of dendritic pruning, neuronal and glial cell number and volume of the medial prefrontal cortex (Markham et al 2007; Koss et al 2014). Therefore early insults such as immune challenge may cause sexual dimorphic disruptions to the MPFC that only appear in adulthood following adolescent maturation of this region and pubertal sex hormone influences (See figure 1 and table 1).…”
Section: Prenatal Immune Challenged Modelmentioning
confidence: 99%
“…This complicated set of differences is difficult to interpret, but there are several factors that likely contributed to our results. First, the prefrontal cortex undergoes significant dendritic pruning and a decrease in volume and neuronal numbers between puberty and adulthood (Van Eden and Uylings, 1985;Markham et al, 2007;Cressman et al, 2010;Koss et al, 2014), so this could explain the reversed seasonal difference in the mPFC of male ground squirrels. The majority of male RGS only survive for a single breeding season (Michener, 1989;Michener and Locklear, 1990b), and as a result of this high mortality, the vast majority of breeding males are significantly older than the non-breeding males.…”
Section: Effect Of Season and Sex-season Interactionsmentioning
confidence: 99%